Gastrointestinal pathophysiology of SARS-CoV2 – a literature review. Issue 6 (1st November 2020) - Syed, Anwaruddin; Khan, Arsalan; Gosai, Falgun; Asif, Abuzar; Dhillon, Sonu
ABSTRACT: SARS-CoV2 is a novel coronavirus responsible for causing COVID-19, first identified in the city of Wuhan, China and officially declared a pandemic by the World Health Organization. SARS-CoV2 expresses high affinity to human ACE2 receptors, including within the gastrointestinal tract. Patients with COVID-19 exhibit a wide spectrum of GI symptoms including anorexia, nausea, vomiting, abdominal pain, and abnormal liver function tests. Pathogenesis behind gastrointestinal symptoms caused by SARS-CoV2 has been postulated to be multifactorial including disruption of the intestinal mechanical barrier integrity, alteration of the gut microbiome and systemic inflammatory response to the virus. SARS-CoV-2 RNA has also been found in stool samples of infected patients for a significantly longer period than in nasopharyngeal samples, though the implication of this finding is unclear at this time. Liver injury in patients with COVID-19 is usually mild, stemming from immune-mediated damage, drug induced hepatotoxicity, or ischemia from sepsis. Patients with pre-existing liver disease may be at a higher risk for hospitalization and mortality. Given the high degree of infectivity of this disease, healthcare providers will need to remain watchful for resurgence of this virus. Strict protocols should be implemented regarding hand hygiene, isolation, personal protective equipment, and appropriate disposal of waste. It is also imperative to identify patients with gastrointestinal symptoms at an early stage as these patients may have a prolonged course between symptom onset and viral clearance.